A Catalyst-Free Synthetic Route to Thiazolo[3,4-a]benzimidazole Derivatives through a Three-Component Reaction - Alizadeh, Abdolali; Bagherinejad, Akram; Moafi, Leila; Zhu, Long-Guan (Synlett, 2016)
A convenient approach for the synthesis of thiazolo[3,4-a]-benzimidazole derivatives has been developed. Three-component reaction of readily available o-phenylenediamines, aryl isothiocyanate, and 4-chloro-3-oxobutanoate in toluene–dichloromethane without any catalyst proceeds under reflux to afford the title compounds in high yields. The structure of the target molecule was confirmed by X-ray diffraction.
Keywords: o-phenylenediamine; aryl isothiocyanate; 4-chloro-3-oxo-butanoate; thiazolo[3,4-a]benzimidazole; multicomponent reaction